Salivary and dental - oral hygiene parameters in 3rd trimester of pregnancy and early lactation: the effect of education - Öztürk, Leyla Koç; Akyüz, Serap; Garan, Aysun; Yarat, Ayşen (Marmara Dental Journal, 2013)
To investigate the effect of 3rd trimester of pregnancy and lactation on dental, oral hygiene and salivary parameters according to educational status. Fourteen healthy women at their 3rd trimester and lactation periods, and 12 non-pregnant women as age-matched controls were recruited. Sulcus bleeding (SBI), plaque (PI) and caries (DMF-T) indexes were estimated and unstimulated whole saliva were taken for free calcium (Ca), inorganic phosphate (Pi), glutathione (GSH),total protein (TP) levels, carbonic anhydrase activity (CA), buffering capacity (BC), flow rate (FR) and pH determinations. Pregnant subjects were also sub-divided as high and low educated sub-groups. DMFT, SBI and PI increased significantly in lactation compared to pregnancy, pH and BC in pregnancy were significantly lower than non-pregnant condition and lactation. Ca and Ca/Pi molar ratio increased and Pi decreased significantly in pregnancy compared to non-pregnant condition. DMF-T, SBI and PI increased; FR and CA decreased significantly in low educated sub-group and SBI and Ca/ Pi molar ratio decreased; pH and BC increased significantly in high educated sub-group in lactation compared to pregnancy. Within the limitation of our sub-groups sample size, daily oral hygiene care and good nutrition seem to have an effective impact on maintaining and/ or improving them between pregnancy and lactation.
Keywords: Salivary parameters;DMFT;SBI;PI;pregnancy;lactation;education